Communication of project risk assessment information through visuals - Irem Dikmen; Elif Karakocak; M. Talat Birgonul (Project Leadership and Society (PLAS), 2024)
Risk assessment is aimed at providing necessary risk-related information to decision-makers for formulating risk mitigation strategies. Poor communication of its context and outputs may lead to misperceptions and wrong judgements. In this research, the role of visualization as an enabler of better communication of risk assessment information is explored using a design science approach. A questionnaire was carried out with project management professionals using the risk report of a case project to understand challenges in interpretation of risk assessment outputs, information and visualization requirements for making better sense of project risk. Based on the findings from the questionnaire, a visual representation, the Risk Box was developed and further tested by semi-structured interviews. Findings reveal that visuals are not only needed for better understanding of probabilistic information but also the context of risk assessment such as relations between individual risks, risk-prone variables, assumptions, scenarios and mitigation strategies.
Keywords: 650; Information; Monte Carlo simulation; Risk communication; Risk management; Visualization